"The ABCs of AD": A prospective evaluation of the efficacy of an educational intervention to increase knowledge of autonomic dysreflexia management among emergency health care professionals. (3rd March 2016) - Krassioukov, Andrei; Tomasone, Jennifer R.; Pak, Melissa; Craven, B. Catharine; Ghotbi, Mohammad H.; Ethans, Karen; Martin Ginis, Kathleen A.; Ford, Michael; Krassioukov-Enns, Dmitri
Abstract : Context/Objective: Despite the availability of consensus-based resources, first responders and emergency room (ER) health care professionals (HCPs) have limited knowledge regarding autonomic dysreflexia (AD) recognition and treatment. The purpose of this study was to assess the efficacy of "The ABCs of AD" educational seminar for improving HCPs' short- and long-term knowledge of AD recognition, diagnosis, and management. Design: Multi-center prospective pre, post, and follow-up questionnaire study. Setting: Level I trauma centers with emergency departments in British Columbia, Manitoba, and Ontario. Methods: ER professionals completed measures immediately before and after ( n  = 108), as well as 3-months following ( n  = 23), attendance at "The ABCs of AD" seminar. Outcome Measures: AD knowledge test; seminar feedback. Results: Following the seminar, participants had higher ratings of their AD knowledge and had significantly higher AD knowledge test scores (M ± SD pre = 11.85 ± 3.88, M ± SD post = 18.95 ± 2.39, out of 22; P < 0.001, d  = 2.21). Most participants believed the seminar changed their AD knowledge, and rated the seminar information as having the potential to influence and change their practice. AD knowledge test scores significantly decreased between post-seminar and 3-month follow-up (M ± SD 3mo = 17.04 ± 3.28; P = 0.004, d  = –0.70); however, 3-month scores remained significantly higher than baseline. Conclusion: "The ABCs of AD" seminar improves HCPs' perceived and actual AD knowledge in the short-term. To enhance knowledge retention in both the short- and long-term, the inclusion of additional active learning strategies and follow-up activities are recommended. The seminar is being translated into an online training module to enhance the dissemination of the AD clinical practice guidelines among first responders, ER staff, and SCI practitioners.